Impact of the Internet on Nepalese Business Environment - Alam, Parwez (Nepalese Journal of Finance, 2024)
This study examines the impact of the internet on Nepalese business environment. Business performance is the dependent variable. The selected independent variables are privacy, responsiveness, decision quality, reliability and efficiency. The primary source of data is used to assess the opinions of the respondents regarding the impact of the internet on business performance. The study is based on primary data with 122 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of internet on business performance in the context of Nepal. The study showed that privacy has a positive impact on business performance indicating that use of secure networks enhance performance of business enterprises. Likewise, reliability has a positive impact on business performance. This implies that higher the level of reliability internet offers, higher would be the performance of business enterprises. Similarly, responsiveness has a positive impact on business performance. It indicates that the responsiveness provided by the internet leads to better business performance. Moreover, efficiency has a positive impact on business performance indicating that higher the level of efficiency of the internet, higher would be the business performance. Likewise, decision quality has a positive impact on business performance which indicates that better decision quality leads to better business performance.